Legal Protection Of Copyright Owners For Error In Persona In Decision No.33/PDT.SUS-Copyright/2018/PN Niaga Jakarta Pusat: Legal Protection Of Copyright Owners For Error In Persona In Decision No.33/PDT.SUS-Copyright/2018/PN Niaga Jakarta Pusat - Rohman, Moh Holilur; Abd Rosid, Abd; Alfiyanti, Afifah (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2023)
Infringements of so many intellectual property rights, especially copyrights, concern and even harm many creators. Decision No. 33/Pdt.Sus-Copyright/2018/PN Similar to the copyright litigation in Niaga Central Jakarta. Copyright owners sue in court for infringement. However, the lawsuit brought by the first-level copyright owner was duly flawed due to a personal error, namely a mispronunciation of Defendant I's name. This also happened with appeals at the level of renunciation. The petition filed by the petitioner will be dismissed because it merely repeats the matters reviewed by Judex Facti. This paper aims to discuss how legal protection for copyright owners against persona errors exists in legal regulations and Islamic law. This study is classified as a normative study. As a result of the discussion, it was concluded that there are no specific rules that provide for legal protection of copyright holders when persona claims are false, and that there is a problem of norm vacuum and that there are no rules. Fix implying issues. Under Islamic law, copyright owners must obtain legal protection in order to generate profits consistent with the purposes of maqasid as-syari'ah, including: preservation of the soul (Hifz al-nafs), preservation of reason (Hifz al-'aql), preservation of property (Hifz al-mal).